Cost-Benefit Analysis of Carbon Tax Policies for the Automotive Industry - Nia Handayani (Manunggal Halim Jaya, 2024)
This study examines the implications of carbon tax policies on the automotive industry, aiming to provide insights into environmental, economic, and social aspects. Employing a qualitative research approach, a comprehensive literature review synthesizes existing studies on carbon taxation and its relevance to the automotive sector. The research design involves systematically identifying and analyzing scholarly articles, policy reports, and industry publications. Thematic analysis is conducted to extract key findings regarding the effectiveness of carbon tax policies, their impact on emissions reduction, economic incentives for innovation, and distributional considerations. The findings indicate that carbon taxes serve as effective market-based mechanisms for internalizing carbon emissions' external costs, driving emissions reductions, stimulating technological innovation, and promoting sustainable mobility transitions. However, the regressive nature of carbon taxes raises concerns about their distributional impacts, necessitating targeted interventions to mitigate disparities and promote social equity. Overall, this study underscores the importance of designing and implementing carbon tax policies that balance environmental imperatives with social considerations to achieve sustainable and equitable outcomes.